The role of metaphors and metonymies in framing the transplantation discourse - Brdar, Mario; Brdar Szabo, Rita (2020)
This article studies figurative uses of metaphors and metonymies utilized to frame the discourse of transplantology. We assume a somewhat wider view of framing than is usually found in the literature and argue that framing effects can be observed on a cline stretching from the private to the institutional pole. We combine this approach with the findings of the prospect theory that distinguishes between gain-framing and loss-framing as two strategic choices in tackling an issue in discourse. The framing tools, as we show in our analysis of authentic materials, in order to be effective need to be adapted to the section of, or the point on, the cline occupied by a particular subtype of discourse. Although the focus in the cognitive linguistic literature is on how conceptual metaphors are employed in framing discourse, we point out that metonymies, interacting with these metaphors, can also play a very important role. The framing tools used in public campaign aimed at winning new organ donors are strategically mostly gain-framed, and as a rule globally based on the gift metaphor. It seems that the metaphorical use of gift as a global choice in institutional contexts is not very efficient since it is too general and vague to make discourse more persuasive at the personal level, as expected in the light of the exemplification theory. This metaphor is more effective when adapted accordingly, as we demonstrated on some campaigns supported by or based on metonymic presentation of various aspects stressing the quality of life after transplantation.
U prilogu se proučava figurativna uporaba metafora i metonimija u uokvirivanju diskursa transplantologije. Polazimo od šireg shvaćanja pojave uokvirivanja od onog koje je općeprihvaćeno u literaturi te tvrdimo da se toj pojavi može pristupiti kao kontinuumu s dva pola: osobnom i institucionalnom. Ovaj se pristup kombinira s teorijom izglednosti unutar koje se postulira gubitno i dobitno uokvirivanje kao dvije strateške mogućnosti izbora. Kako bi bila svrsishodna, sredstva koja se rabe za uokvirivanje, kako pokazujemo na autentičnim materijalima, trebaju se prilagoditi odsječku kontinuuma na koji se može smjestiti određeni podtip diskursa. Iako je u kognitivno lingvističkoj literaturi naglasak gotovo uvijek na ulozi metafore u uokvirivanju diskursa, ističemo da i doprinos metonimije, u suradnji s metaforama, može biti od velikog značaja. Sredstva koja se rabe zauokvirivanje u javnim kampanjama kojima je cilj pridobivanje novih donora organa u pravilu se temelje na konceptualnoj metafori poklona. Pokazuje se da metaforička uporaba koncepta poklona kao globalnog izbora u institucijskim kontekstima nije učinkovita jer je preopćenita i neodređena a da bi mogla biti uvjerljiva na osobnom nivou, kao što se i može predvidjeti u okviru teorije oprimjerivanja. Spomenuta je metafora učinkovitija kada se prikladno prilagodi, kako pokazujemo na nekim primjerima kampanja koje su poduprte ili se temelje na metonimijskom prikazu različitih aspekata koji naglašavaju kvalitetu života nakon transplantacije.
Bibliografske bilješke uz tekst ; bibliografija: str. 338-343.
Summary
Keywords: Metafora -- Metonimija -- Zdravstveni diskurs -- Uokvirivanje